PENGARUH LATIHAN BENCH PRESS TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA ATLET TINJU DENPAL BOXING CAMP PEKANBARU - Maria Artauli; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem of this research are some shortcomings, especially in physical condition, muscle strength of arms and shoulders seen when they are practicing sedo boxing, samsak, and at the time of sparing. Can be seen at the time of athlete Dreal Patner a lot of punches in catapult boxing athletes do not have the weight of a punch that means that the opponent does not change the position but returns back punch. The type of this research is experimental treatment (Experimental), this research population is athlete denpal boxing camp Pekanbaru, the sample in this research is the entire population of 5 people. The data retrieval technique can be from pre-test and post-test. The instrument performed in this research is an expanding dynamometer test, which aims to measure arm and shoulder muscles strenght. Variables that exist in this research is bench press exercise which is denoted by X as independent variable, while muscle strength of arm and shoulder is denoted by Y as dependent variable. After that, the data were processed with statistics, to test the normality by liliefors test with a significant level of 0.05. The hypothesis proposed is the effect og bench press exercises on the strength of the arms and shoulder muscles at Pekanbaru boxing Denpal boxing camp athletes. Based on T test analysis, the conclusion is obtained: Tcount of 2.053 and Ttable 2.015, means Tcount > T table. It can be concluded that Ho is rejected and Ha accepted, this concludes that there is significant effect between bench press exercise on strength of arm and shoulder muscles at athlete Denpal boxing camp Pekanbaru.Key Words: Bench Press, Arm and Shoulder Muscle Strength